Efficient, informed and competitive market: The Malaysian regulation on takeovers and mergers of companies - Ambaras Khan, Mushera Bibi; Moiden, Azza Isma; David Moreira, Sharon; Khairuddin, Azhana (Thomson Reuters Malaysia Sdn Bhd, 2013)
Sharers' protection is at the nucleus of all takeovers and mergers exercise. The requirement to protect and to ensure fair treatment of shareholders has been constantly considered significant. One of the most imperative rationales pertaining to this is to ensure that the market for corporate control functions in an efficient, informed and competitive manner. The basis of a fair and efficient market is built upon practising and sustaining proper disclosure, whereby investors are able to make informed decisions about their choice of investments. In order to ensure that the same is achieved and accomplished, the company's transition of control has to occur in an efficient, informed and competitive market and the shareholders are duly given the rights to reasonable and equal opportunities to participate in any benefits available in a takeover offer. This article seeks to study Malaysian takeovers' regulatory framework which encourages and efficient, informed and competitive market, namely the Capital Market Service Act 2007 and in particular the significant changes to the Malaysian Code on Takeovers and Mergers 2010. The key amendments are, inter alia, on the extension of the said 2010 Code to scheme on arrangement, compromise, amalgamation, selective capital reduction and REITs, announcement of takeover offer, prohibitions as to frustration of takeover offer, persons acting in correct, voluntary general offer ( in terms if interpretation of the term "good faith"0, independent adviser, privatisation of listed companies via asset disposal, friendly defence mechanisms as well as duties of the board of directors. This article also examines the challenge and/or impediments shrouding the regulatory framework and authority vis-a-vis and efficient, informed and competitive market in Malaysia takeovers, namely one involving mandatory offer, deal protection measures, scheme of arrangement, competition laws, interpretation of terms, i.e "good faith" just and equitable" and "cash consideration", and also on the lack of independency of the adviser. This article further compares the practices in Malaysia with those in other countries such as the United Kingdom as well as analyses the divergent views of jurists, namely the vies of Mannolini and Greenwood on the one hand and of Sheehy on another (i.e the former depending equity principles whereas the latter, in support of economic efficiency), Malaysian takeover laws relevant to the efficient, informed and competitive market. The practices and view, inter alia, pondered upon in arriving at the conclusion that the available resource is that public interest prevails and shareholders' interests rule the day.